On limit theorems for weakly dependent random variables - Riauba, B. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Б. Ряуба. О предельных теоремах для слабо зависимых случайных величин B. Riauba. Ribinių teoremų silpnai priklausomiems atsitiktiniams dydžiams klausimu